The impact of overtraining, training volume and injuries on well-being among gymnasts in Iceland - Birta Sól Guðbrandsdóttir 1994- (2019)
Well-being among athletes is an important factor which has received increased attention during recent years. Studies have shown that injuries, training volume, and overtraining can have an impact on athletes’ well-being by increasing symptoms of depression and anxiety. Therefore, the aim of the current study was to examine the impact of injuries, training volume and overtraining on the symptoms of depression and anxiety among gymnasts in Iceland. The participants in the study were 34 gymnasts between 18 - 29 years old in both artistic and team gymnastics. The majority of the participants were women (79.4%) and on the Icelandic national gymnastics team (55.9%). The participants answered a questionnaire which included questions on training volume, injuries, overtraining, symptoms of depression and anxiety, as well as demographics. The results of the study showed that 47.1% of the gymnasts had mild to moderate symptoms of depression and 58.9% had mild to moderate symptoms of anxiety. The results also showed that gymnasts who experienced overtraining had higher levels of anxiety and depression compared to those who did not experience overtraining. Neither injury nor training volume impacted levels of anxiety and depression among the gymnasts. These results show that anxiety and depressive symptoms can be found among Icelandic gymnasts and therefore it is important to discuss the impact these factors can have on gymnasts’ well-being. Keywords: well-being, gymnasts, anxiety, depression, injury, training volume, overtraining Andleg heilsa hjá íþróttafólki er mikilvæg og hefur henni verið veitt meiri athygli á síðastliðnum árum. Rannsóknir sýna að meiðsli, æfingaálag og ofþjálfun getur haft áhrif á andlega heilsu meðal íþróttafólks með því að auka kvíða og þunglyndi. Markmið núverandi rannsóknar var að athuga áhrif meiðsla, æfingaálags og ofþjálfunar á einkenni kvíða og þunglyndis. Þátttakendur voru 34 fimleikaiðkendur, á aldrinum 18 - 29 ára, í bæði áhaldafimleikum og hópfimleikum. Meirihluti þátttakenda var konur ...